2018
DOI: 10.21307/jofnem-2018-017
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Weeds, Solanum nigrum and Datura stramonium

Abstract: We investigated Solanum nigrum (seeds) and Datura stramonium (shoots) against root-knot nematodes in terms of J2 paralysis and egg hatch inhibition (methanol extract), as well as inhibition of nematode development in host roots (soil amending with either S. nigrum seeds' or D. stramonium shoots' meal). Datura stramonium was found equally effective at inhibiting motility of Meloidogyne incognita and Meloidogyne javanica (both EC 50 = 427 μ g mL-1 at 3 day), but inhibition occurred more quickly for M. incognita … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…While spore suspensions of S. monomycini ATHUBA 220 and S. colombiensis ATHUBA 438 could alleviate the nematode burden of M. incognita in Col-0 and fra2 ( Figure 3 A) respectively, to our surprise, this was not the case for M. javanica , where S. colombiensis ATHUBA 438 and S. monomycini ATHUBA 220 were ineffective ( Figure 3 B). Additionally, it has previously been demonstrated that M. javanica is more difficult to control than M. incognita [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While spore suspensions of S. monomycini ATHUBA 220 and S. colombiensis ATHUBA 438 could alleviate the nematode burden of M. incognita in Col-0 and fra2 ( Figure 3 A) respectively, to our surprise, this was not the case for M. javanica , where S. colombiensis ATHUBA 438 and S. monomycini ATHUBA 220 were ineffective ( Figure 3 B). Additionally, it has previously been demonstrated that M. javanica is more difficult to control than M. incognita [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…in control]} × 100 [32]. Data was subjected to probit linear regression analysis and the concentration of nanoparticles (EC 50 values) required for 50% death/paralysis of nematodes was calculated.…”
Section: Discussionmentioning
confidence: 99%
“…However, ethanol extract was more effective than aqueous extract. Oplos et al, (2018), reported that methanol extract of D. stramonium was effective in decreasing the egg hatching and cell division in M. incognita eggs. In a recent study by Moazezikho et al, (2020), mentioned that D. stramonium presents a good inhibitory effect in M. javanica egg hatching.…”
Section: Laboratory-tomatomentioning
confidence: 99%
“…In, India, Shah et al, (2018), illustrated that application with 10 and 20 ml water leaf extracts of D. metel (50 gm fresh leaves/ 500ml distilled water) was effective in controlling the root knot in Brinjal (Solanum melongena) and reduced the number of M. incognita juveniles in pot soil, number of females and root galling index. On the other hand, Oplos et al, (2018), in Greece evaluated the nematicidal effect of incorporating D. stramonium shoots in infested soil on inhibition of root-knot nematodes in tomato plants. Results cleared those treatments with D. stramonium powder reduced the nematodes densities in tomato roots as well as gall formation was significantly suppressed.…”
Section: Laboratory-tomatomentioning
confidence: 99%